Arthroscopic treatment of chronic wrist pain after distal radius fractures. Issue 38 (18th September 2020) - Lee, Young-Keun; Kwon, Tae-Young; Lee, Ha-Song
Abstract : Abstract: We report the arthroscopic and clinical findings of patients with chronic wrist pain following distal radius fracture (DRF) who underwent diagnostic arthroscopy and arthroscopically-assisted tailored treatment. We retrospectively analyzed the records of 15 patients with chronic wrist pain following DRF, who underwent diagnostic arthroscopy and arthroscopically-assisted tailored treatment from 2010 to 2017. The average patient age was 44 years (range, 20–68 years), average time from injury to treatment 21 ± 23.46 months (range, 3–96 months) and average follow up period 20.13 ± 8.71 months (range, 12–39 months). The functional outcome was evaluated by comparing the preoperative and final follow up values of the range of motion, grip strength, pinch strength, visual analogue scale for pain and quick disabilities of the arm, shoulder and hand score. Based on the arthroscopic findings, synovitis was found in all cases and the pathologic intra-articular lesions were classified into 4 patterns. Triangular fibrocartilage complex rupture was seen in 14 cases, intercarpal and radiocarpal ligament ruptures in 9 cases, ulnar impaction syndrome in 5 cases, and cartilage lesion in 9 cases. In terms of surgical treatment, 15 patients underwent arthroscopic synovectomy, 7 foveal or capsular repair of TFCC, 7 intercarpal Kirschner wires fixation or intercarpal thermal shrinkage, 1 intercarpal ligament reconstruction, 2 Sauve-Kapandji procedure, and 2 unlar shortening osteotomy. Postoperatively, the average range of motion, grip strength, and pinch strength increased significantly. From preoperative to final follow up values, the average visual analogue scale and quick disabilities of the arm score decreased from 5.93 ± 1.58 (range, 3–8) to 1.33 ± 1.29 (range, 0–3) ( P  = .001) and from 49.38 ± 19.09 to 12.63 ± 7.63 ( P  = .001), respectively. Diagnostic arthroscopy and arthroscopically-assisted tailored treatment of chronic wrist pain following DRF can provide an accurate diagnosis, significant pain relief, and functional improvement.